Adaptive reuse and authenticity: promoting urban conservation in Melaka's historic town - Angela Wee Kah Man (Journal of City: Branding and Authenticity, 2023)
This study investigates the impact of adaptive reuse on the sense of place and urban conservation in Melaka's historic town, where heritage shophouses have been repurposed as F&B establishments. Questionnaire surveys were used to collect data from stakeholders, including local communities, to assess their perceptions of adaptive reuse works. The study found that adaptive reuse works had a positive impact on the sense of place and urban conservation in Melaka's historic town. However, the preservation and adaptation of these buildings must be done with proper community engagement to avoid alienating locals from their built environment. Discussions with stakeholders revealed that a holistic approach that considers both heritage preservation and community needs is crucial in promoting sustainable and inclusive urban conservation practices. The study concludes that adaptive reuse works on heritage shophouses as F&B establishments can contribute to sustainable urban conservation and promote an authentic city brand. Community engagement is crucial in preserving the character of these buildings and ensuring the inclusion of locals in their built environment. By incorporating community input, adaptive reuse works can promote a sense of place and belonging that contributes to the overall urban conservation and sustainability of the city. The adaptive reuse of heritage shophouses as F&B establishments is becoming increasingly popular, contributing to the area's status as a UNESCO World Heritage City. However, the preservation and adaptation of these buildings must be done in a way that reflects the local community's values and needs to avoid alienating them from their built environment. By prioritizing community engagement and consultation, adaptive reuse works can promote sustainable urban conservation practices, enhance the city's authenticity, and contribute to a sense of place and belonging for both locals and visitors.